Pengaruh Konten, Live Streaming, dan Diskon terhadap Keputusan Pembelian Produk “Niu Me Hairclip” Melalui Platform Media Sosial - Jayawardani Januari Christie; Adhita Maharani Dewi (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
The rapid growth of social media has encouraged micro, small, and medium enterprises (MSMEs) to adopt digital marketing strategies to attract consumers more effectively. However, many MSMEs still face difficulties in optimizing social media features such as content creation, live streaming, and promotional pricing to influence consumer purchasing decisions. This study aims to examine the effect of social media content, live streaming, and discounts on purchasing decisions for “Niu Me Hairclip” products through TikTok. The research used a quantitative approach with a survey method involving consumers in the Jabodetabek area who had interacted with the product on social media. Data were collected through online questionnaires using a Likert scale and analyzed using multiple linear regression. The results indicate that discounts have a significant positive effect on purchasing decisions, while content and live streaming do not show significant partial effects. Nevertheless, all variables simultaneously influence purchasing decisions. These findings suggest that price incentives remain the main factor driving consumer purchases, while digital communication elements support consumer awareness and trust in social commerce activities.